Komunikasi Transdental dalam Ibadah Suluk - Muhammad Shiddiq Al Ghifari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research will discuss Transdental Communication in Suluk Worship, namely communication that occurs between humans and God. The aim of this research is to describe the experiences experienced by the Suluk congregation through the Dhikr that is practiced when entering Suluk. This research is centered on one of the Dayah in Aceh Besar, namely Dayah Darul Ulum Abu Leung Ie, which is led by Tengku T. Tajuddin Usman Al-Fauzi who is the son of the great cleric, namely Abu Usman Al-Fauzi and a direct student of Abuya Muda. Waly Al-Khalidy. In this research, the type of research used is qualitative research. Methods for collecting data are through observation and interviews. The results of the research show that by carrying out transcendental communication with Allah, the Suluk congregation feels calmer and closer to Allah, and their emotions are easily controlled, they are not easily influenced by bad actions, and they can easily forgive others.